Perception and preventive behavior during COVID-19 pandemic among urban residents in Banda Aceh, Indonesia: a cross-sectional study (Medical Journal of Indonesia, 2021)
BACKGROUND It is critical to evaluate the perception and preventive behavior of COVID-19 to formulate the optimal public health strategies for tackling the ongoing pandemic. This study aimed to enhance knowledge on the perception and preventive behavior toward COVID-19 among urban residents in Banda Aceh, Indonesia. METHODS A cross-sectional population-based survey was conducted from September to October 2020 using a structured questionnaire for the attendants of the six public health centers in Banda Aceh. Information about sociodemographic, perception, and preventive behavior toward COVID-19 were collected. The data were analyzed to find the association between the level of preventive behavior and covariates. RESULTS Among 1,067 respondents, 71.1% were female, 52.5% were aged between 40 and 60 years, 31.2% were university graduates, and >60% were unemployed with underlying diseases such as diabetes, hypertension, and cardiopulmonary diseases. The responses of each statement toward COVID-19 were varied. The multivariable model of covariates showed that females had good preventive behavior toward COVID-19 (adjusted OR: 1.849, 95% CI: 1.359–2.515). Urban residents in Banda Aceh with the underlying diseases had poor preventive behavior, while those with higher educational level and perception scores were more inclined to engage in good preventive behavior. CONCLUSIONS Most urban residents in Banda Aceh showed positive perception and propensity for adopting preventive measures. Health education is necessary for susceptible residents, such as males, less educated people, and people with underlying diseases. It should be stressed on specific practices and knowledge.